2016
DOI: 10.1002/gcc.22432
|View full text |Cite
|
Sign up to set email alerts
|

Anchored multiplex PCR for targeted next‐generation sequencing reveals recurrent and novel USP6 fusions and upregulation of USP6 expression in aneurysmal bone cyst

Abstract: Primary aneurysmal bone cyst (ABC) is a neoplastic process due to recurrent translocations involving the USP6 gene. By fluorescence in situ hybridization, up to 69% of primary ABCs harbored USP6 translocations; no USP6 translocation was found in secondary ABC or giant cell tumor of bone (GCT). GCT can recur locally, metastasize to the lungs in some cases, and rarely undergo malignant transformation. Differentiating primary ABC from its mimics is important for treatment and prognosis. We evaluated USP6 fusion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 31 publications
(41 reference statements)
4
72
0
Order By: Relevance
“…In our series, all of the 11 consecutive primary ABCs harbored USP6 gene rearrangement, as revealed by NGS. Similarly, Guseva et al reported a series of 13 primary ABCs, all of which harbored USP6 gene rearrangements . Although the number of cases in both series combined is not very large, it is reasonable to conclude that USP6 gene rearrangement is consistently present in all ABCs and that ABCs are defined by the presence of a USP6 fusion.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our series, all of the 11 consecutive primary ABCs harbored USP6 gene rearrangement, as revealed by NGS. Similarly, Guseva et al reported a series of 13 primary ABCs, all of which harbored USP6 gene rearrangements . Although the number of cases in both series combined is not very large, it is reasonable to conclude that USP6 gene rearrangement is consistently present in all ABCs and that ABCs are defined by the presence of a USP6 fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Although the number of cases in both series combined is not very large, it is reasonable to conclude that USP6 gene rearrangement is consistently present in all ABCs and that ABCs are defined by the presence of a USP6 fusion. This may be important when a primary ABC needs to be differentiated from its potential mimics, including giant cell tumor, chondroblastoma, osteoblastoma, nonossifying fibroma and rarely malignant tumors, such as telangiectatic osteosarcoma . FISH and RT‐PCR methods may fail to recognize a USP6 gene fusion if the fusion partners are located too close, an inversion of the gene is involved, or the USP6 ‐fusion partner is unknown .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations